2013
DOI: 10.1182/blood-2012-01-404889
|View full text |Cite
|
Sign up to set email alerts
|

Spleen endothelial cells from patients with myelofibrosis harbor the JAK2V617F mutation

Abstract: Increased microvessel density contributes to abnormal BM and spleen microenvironment in myelofibrosis (MF). Taking advantage of the JAK2V617F mutation as a marker of malignancy, in the present study, we investigated whether splenic endothelial cells (ECs) obtained from capillaries by laser microdissection or from fresh spleen tissue by cell culture or cell sorting harbored such mutation in patients bearing the mutation in their granulocytes and undergoing splenectomy for therapeutical reasons. To extend the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 38 publications
3
100
0
Order By: Relevance
“…1519 JAK2 V617F mutation is also present in ECs isolated by microdissection from liver and spleen samples of patients with MPNs. 17,20 In addition, we and others have shown that JAK2 V617F ECs are critical in the development of the bleeding abnormalities in a murine model of JAK2 V617F -positive MPNs in which JAK2 V617F is expressed in all hematopoietic cells and endothelial cells. 21 All of these observations suggest that ECs are involved in the pathogenesis of MPNs.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…1519 JAK2 V617F mutation is also present in ECs isolated by microdissection from liver and spleen samples of patients with MPNs. 17,20 In addition, we and others have shown that JAK2 V617F ECs are critical in the development of the bleeding abnormalities in a murine model of JAK2 V617F -positive MPNs in which JAK2 V617F is expressed in all hematopoietic cells and endothelial cells. 21 All of these observations suggest that ECs are involved in the pathogenesis of MPNs.…”
Section: Introductionmentioning
confidence: 84%
“…16,17,20 In addition, ECs are an important niche component of the extramedullary (splenic) hematopoiesis, which is almost always present in patients with MPNs and is associated with MPN disease progression. 13,14 All of these observations suggest that ECs are involved in the malignant process leading to MPNs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, endothelial-mesenchymal transition and the resulting endothelial cell fate have been recently implicated in the pathogenesis of PMF. 30, 31, 32 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, VEGF-induced Ca 2þ inflow is remarkably higher in breast cancer-derived ECs than in normal cells [30]. We recently isolated spleen ECs from PMF patients bearing the JAK2 mutation [31]. It will be interesting to assess whether and how the Ca 2þ response to VEGF is altered also in these cells.…”
Section: Resultsmentioning
confidence: 97%